О ПРОГРАММНО-АППАРАТНЫХ ИЗМЕРИТЕЛЬНЫХКОМПЛЕКСАХ И ИХ ВОЗМОЖНОСТЯХ/ОСОБЕННОСТЯХ ВПРОМЫШЛЕННОСТИ - Баймуратов, О.А.; Кангожин, Б.Р.; Даутов, С.С. (Journal of Emerging Technologies and Computing, 2021)
Preventing energy losses and optimizing product lifecycleenergy management are of paramount importance to address the increased globaladverse environmental impacts. It is expected that energy savings will beachieved both by improving the energy efficiency of individual productionprocesses, and through the use of effective energy monitoring and managementsystemsSolving the problem of timely detection of losses and its correctelimination in many production enterprises is difficult due to insufficientawareness of energy consumption. One of the solutions to this problem is thestudy and development of the functional capabilities of software and hardwaremeasuring systems and their purpose.This article presents examples and capabilities of software and hardwaremeasurement systems for the purpose of forming a model of energy efficiency.